2011
DOI: 10.1038/msb.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin‐driven regulatory circuit controls quality and timing of mRNA decay in inflammation

Abstract: Inflammatory gene activation must be rigorously controlled to ensure a rapid, but transient, response. In this work, a regulatory circuit is revealed that governs the destabilization of inflammatory mRNAs and plays an essential role in re-establishing immune homeostasis after inflammatory stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
152
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(164 citation statements)
references
References 54 publications
11
152
1
Order By: Relevance
“…In monocytes, a dependence of LPS-induced AKT activation on class I A of the three PIK3 classes (Cantley 2002) has been shown by RNAi-mediated PIK3CA silencing (Lee et al 2007). In contrast, RIP-Chip experiments with untreated macrophages and after LPS-activation employing an antibody against TTP revealed that TTP modulates the inflammatory response by controlling the stability of mRNAs, which encode pro-and antiinflammatory cytokines (Stoecklin et al 2008;Kratochvill et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In monocytes, a dependence of LPS-induced AKT activation on class I A of the three PIK3 classes (Cantley 2002) has been shown by RNAi-mediated PIK3CA silencing (Lee et al 2007). In contrast, RIP-Chip experiments with untreated macrophages and after LPS-activation employing an antibody against TTP revealed that TTP modulates the inflammatory response by controlling the stability of mRNAs, which encode pro-and antiinflammatory cytokines (Stoecklin et al 2008;Kratochvill et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Tissuespecific deletion of Ttp using Ttp fl/fl LysM-Cre animals (referred to herein as TTP ΔM mice) demonstrated an essential function for myeloid TTP expression in the protection against LPS-induced toxic shock (12,16), but the role of TTP in immune responses to live pathogens has not been elucidated. To this end, we used a mouse model of invasive soft tissue infection with S. pyogenes.…”
Section: Ttp Ablation In Myeloid Cells Protects the Host Against Invamentioning
confidence: 99%
“…The inflammatory symptoms are reduced upon blockage of TNF or IL-23 (14,15), but it remains possible that these cytokines act together or downstream of other defects resulting from TTP deficiency. Mice with LysM-Cre-driven Ttp deletion in macrophages and neutrophils are healthy despite an increased susceptibility to endotoxin-mediated septic shock (12,16). The role of TTP during bacterial infection and its specific function in neutrophils remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shift assays with AU-rich and Random-RNAs (Kratochvill et al 2011) were performed basically as described in Tiedje et al (2012). To improve the shifts using 10 µg of HEK293T lysates overexpressing the indicated proteins, 20 µg of yeast tRNA in combination with 10 µg of salmon sperm DNA were preincubated with the lysates for 30 min prior to the addition of the DY681 and DY781-5 ′ labeled RNAs.…”
Section: Rna-emsamentioning
confidence: 99%